1993
DOI: 10.1136/jnnp.56.12.1271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vigabatrin on sedation and cognitive function in patients with refractory epilepsy.

Abstract: Twenty-four patients with refractory epilepsy on one or more antiepileptic drugs were given additional vigabatrin (1 g twice daily for six weeks, followed by 1-5 g twice daily for a further six weeks) and matched placebo in a double blind, randomised, crossover study. A battery of neuropsychological tests was administered at baseline and at weeks two, six and 12 of both treatment periods. No significant differences were found between vigabatrin and placebo at any time point for any of the objective tests of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Patients who attained TGB monotherapy improved in the areas of adjustment and mood (67), a change attributable most likely to discontinuation of previous AEDs. Similarly, several investigations of the cognitive and behavioral effects of VGB have shown no or only minimal impairment, and even some evidence of improvement (68)(69)(70)(71)(72). Psychosis and depression have been repeatedly described with VGB, both in adults and in children (73)(74)(75).…”
Section: Newer Aedsmentioning
confidence: 92%
“…Patients who attained TGB monotherapy improved in the areas of adjustment and mood (67), a change attributable most likely to discontinuation of previous AEDs. Similarly, several investigations of the cognitive and behavioral effects of VGB have shown no or only minimal impairment, and even some evidence of improvement (68)(69)(70)(71)(72). Psychosis and depression have been repeatedly described with VGB, both in adults and in children (73)(74)(75).…”
Section: Newer Aedsmentioning
confidence: 92%
“…Vigabatrin has demonstrated few CAEs when compared with placebo in double-blind studies [Dean et al 1999;Dodrill et al 1993;Gillham et al 1993] and fewer adverse effects than carbamazepine in a small, open-label, randomized, parallel-group study . Vigabatrin had no detrimental effects on cognitive functions at 12 months, and memory retrieval and mental flexibility improved significantly.…”
Section: Vigabatrinmentioning
confidence: 99%
“…In four studies assessors were blinded to some but not all of the outcomes assessed. [48][49][50][51] 7. Were those individuals who administered the intervention blinded to the treatment allocation?…”
Section: Were the Outcome Assessors Blinded To The Treatment Allocation?mentioning
confidence: 99%
“…38,51,87,[152][153][154]168,169 Twenty-two studies were parallel superiority trials and 10 were crossover trials. No studies of adjunctive OXC reported QoL outcomes.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation